2017
DOI: 10.1007/s10695-016-0337-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and immune response characterizations of a novel Bax inhibitor-1 gene in pufferfish, Takifugu obscurus

Abstract: Apoptosis plays a crucial role in many biological processes, including development, cellular homeostasis, and immune responses. Bax inhibitor-1 (BI-1) is an anti-apoptotic protein that protects cells from endoplasmic reticulum stress-induced apoptosis. In this study, a BI-1 gene from the pufferfish Takifugu obscurus (Pf-BI-1) was identified and characterized. The full length of Pf-BI-1 cDNA was 1387 bp, including a 5'-UTR of 82 bp, a 3'-UTR of 591 bp containing a poly-(A) tail, and an open reading frame (ORF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The mRNA expression was notably increased, indicating that ToTNFα might be involved in p53-related apoptosis. Further, the BI-1, an anti-apoptotic protein, was determined (Cheng et al, 2017). Our results showed that In summary, our research indicated that the ToTNFα was conserved in structural characterization and functional identification.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…The mRNA expression was notably increased, indicating that ToTNFα might be involved in p53-related apoptosis. Further, the BI-1, an anti-apoptotic protein, was determined (Cheng et al, 2017). Our results showed that In summary, our research indicated that the ToTNFα was conserved in structural characterization and functional identification.…”
Section: Discussionmentioning
confidence: 62%
“…The mRNA expression was notably increased, indicating that ToTNF‐ α might be involved in p53 ‐related apoptosis. Further, the BI‐1, an anti‐apoptotic protein, was determined (Cheng et al., 2017). Our results showed that (r)ToTNF‐ α stimulation notably up‐regulated BI‐1 mRNA expression of head kidney leucocytes, indicating that ToTNF‐ α might induce apoptosis depending on anti‐apoptotic protein BI‐1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations